Epithelial-mesenchymal transition in сolorectal adenocarcinoma progression - M. A. Shyshkin; S. V. Fen (Zaporožskij Medicinskij Žurnal)
Aim – to analyze immunohistochemical expression levels of epithelial and mesenchymal phenotype markers in colorectal adenocarcinoma on I–IV stages (pTNM).